Formalization of the planning process for construction organization - Шевчук, О. А. (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2013)
The article is devoted to formalization of planning process of Building and construction organizations (BCO), which will allow develop a system of decision-making in the planning of a construction company. This paper contains the analysis of the construction and mounting company as a management object, the describtion of the levels of management BCO, the formulation of the functional aim.